Pengetahuan dan Penerapan Tri Hita Karana dalam Subak untuk Menunjang Pertanian Tanaman Pangan Berkelanjutan (Kasus Subak Mungkagan, Desa Sembung, Kecamatan Mengwi, Kabupaten Badung) - ANDIKA, I PUTU TESSA; SUDARTA, WAYAN; DJELANTIK, A.A.A WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.2, April 2017, 2017)
Thesis Title "Knowledge and Application of Tri Hita Karana in Subak to Support Sustainable Horticulture Food Agriculture (The Case of Subak Mungkagan, Sembung Village, Mengwi, Badung Regency)" Bali historically owns traditions, culture and religious commitment of its own in the form of an organization called Subak. All Subaks in Bali apply the concept of Tri Hita Karana one of them being Subak Mungkagan. The purpose of this research was to determine the level of knowledge, and the farmers’ application of Tri Hita Karana in Subak Mungkagan to support sustainable crop farming, in the village of Sembung, Mengwi, Badung regency. Subak Mungkagan population numbered 161 people. The determination of samples used quota sampling and random sampling. The respondents taken amounted to 32 people. The results showed that the farmers’ knowledge of Tri Hita Karana in Subak Mungkagan to support sustainable horticulture agriculture, village Sembung, Mengwi, Badung belonged to the excellent category by achieving a score of 4.28. The level of implementation of the Tri Hita Karana by farmers in Subak Mungkagan to support sustainable food crops, also belonged to the excellent category by achieving a score of 4.17. Based on the research it can be suggested the existence of sanctuaries and their use has been complete, what needs to be considered is the cleanliness after praying in the temple area. Extension in Subak Mungkagan is only done twice a year, it should have been done five times a year, so that knowledge and application of Tri Hita Karana aspects Palemahan in particular in Mungkagan Subak is related to the relationship of Subak members with the surrounding environment.
Keywords: knowledge; application; Tri Hita Karana; subak